(untitled) (Western Journal of Medical and Biomedical Sciences, 2025)
Ketamine is a highly liposoluble phenylcyclohexylamine derivative consisting of an (R) and (S) enantiomer. Ketamine can be administered through intravenous, intramuscular, intrarectal, oral, intranasal, intrathecal, or epidural routes. Intravenous ketamine has been studied as an adjunct in multimodal analgesia, but there are still knowledge and experience gaps regarding neuraxial ketamine. This study aimed at studying the anaethetic and analgesic potency of ketamine when administered intrathecally as adjunct to bupivacaine in subarachnoid blocks. Sixty patients after ethical approval and consent were randomized into two groups of thirty patients each; B (bupivacaine only) and BK (bupivacaine plus Ketamine). Intervention medications were prepared in two syringes 2.5mls each with the researcher blinded of the contents... The contents were given intrathecally during institution of subarachnoid blocks. Variables like onset of sensory and motor blocks, duration of blocks, time to first analgesic request, frequently of analgesics and incidence of side effects were sought for. The bupivacaine plus Ketamine group had a faster and longer duration of sensory and motor blocks with longer time to first analgesic request and minimal frequency of rescue analgesics. There was no incidence of serious side effects except for few incidences of elevated systolic / diastolic pressures. Ketamine when given intrathecally as adjuvants to bupivacaine during subarachnoid blocks offers anaesthetic and analgesic potency.